Measurements of dielectric constants and loss tangents of metal-backed concrete specimen using a zero finding technique/ Mohd Noor Hashim - Hashim, Mohd Noor (1998)
A free space microwave measurement system is used for the high temperature measurement of dielectric constant and loss tangent of homogeneous material and is applicable to composite materials as well. Since the existence of moisture in concrete is a major cause of damage to pavements and other concrete structures, there is an increasing need for non-destructive detection and monitoring of moisture content before failure occurs. Thus, this measurement system operating in the 8.0 -12.5 GHz frequency range is used for reflection coefficient, (Sn) measurement of concrete samples at room temperature. The dielectric constant and loss tangent values are calculated from the measured data using a zero finding technique. Dielectric properties are correlated to water content by dielectric mixture theory. Water content will be measured for different wet specimen of concrete, with varying the value of air void content. Key components of measurement system are Spot-focusing hom lens antennas, Wiltron Vector Network Analyzer, Mode transition, Computer and Printer. Errors due multiple reflections between antennas via the surface of the sample are corrected by using a free space LRL (Line, Reflect, Line) calibration technique.